MCDA/M in Telecommunication Networks - Challenges and Trends - Clímaco, João (2019)
The extremely rapid evolution of new telecommunication technologies and services and its interaction with a complex socio-economic environment, justifies the increasing interest in applying multi-criteria evaluation approaches in a wide variety of decision making processes involved in network planning and design. After a brief overview of critical evolutions in telecommunication network technologies and services, an outline analysis of issues and difficulties concerning the applications of multi-criteria decision aiding/making (MCDA/M) in telecommunication network planning and design, is described. Also highlights on more relevant or recent contributions of this type, in network design and planning models, including strategical and policy issues, will be presented. Finally, an analysis and outline discussion of current and future research trends and challenges concerning the use of multi-criteria approaches in these areas, is put forward.